2013
DOI: 10.1177/2048872613517370
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of atrial fibrillation in acute coronary syndromes: results from the ARIAM registry

Abstract: These findings suggest that the presence of new-onset AF during ACS is associated with a significant increase in mortality, even after adjusting for confounding variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 39 publications
5
44
0
1
Order By: Relevance
“…10,11) In previous studies, patients with permanent AF or new onset AF had higher rates of CV mortality as well as readmission for HF in AMI, irrespective of STEMI or NSTEMI. [9][10][11] Patients with AF often have multiple comorbidities, for example, older age, small body weight, hypertension, left ventricular hypertrophy, and/or ventricular systolic dysfunction. 26) With these clinical characteristics, AF patients are vulnerable to HF and cardiogenic shock in the initial phase of AMI, and suffer prevalent events of bleeding and major arterial embolism during the chronic phase of MI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11) In previous studies, patients with permanent AF or new onset AF had higher rates of CV mortality as well as readmission for HF in AMI, irrespective of STEMI or NSTEMI. [9][10][11] Patients with AF often have multiple comorbidities, for example, older age, small body weight, hypertension, left ventricular hypertrophy, and/or ventricular systolic dysfunction. 26) With these clinical characteristics, AF patients are vulnerable to HF and cardiogenic shock in the initial phase of AMI, and suffer prevalent events of bleeding and major arterial embolism during the chronic phase of MI.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical reports, such as the HORIZONS-AMI study, 10) have reminded us of the importance of AF in AMI or STEMI populations. However, these data had some limitations, such as relatively advanced age, 8) mixed population of ACS, 9) and only including new onset AF that occurred after primary PCI. 10,11) To overcome these limitations, we selected STEMI patients who arrived at the ER within 12 hours after chest pain onset and underwent primary PCI within 90 minutes after ER arrival from the KAMIR database to reflect the real situation of modern treatment modalities for STEMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particularities of this registry have been previously described. [16] In brief, demographic, laboratory, and angiographic variables and occurrence of clinical events during the hospital course were collected from patients with definitive diagnosis of ACS admitted to Coronary Care Units of 49 centers through an online platform (www.ariam-andalucia.org). Patients with ACS in whom an invasive approach (coronary angiography) was performed during admission M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 and who received clopidogrel constituted the study population.…”
Section: Methodsmentioning
confidence: 99%
“…7 Of note, according to the ARIAM Andalucia Study, the propensity score analysis revealed that only new-onset AF persisted as an independent predictor for death, and that MACE were more frequent in new-onset AF than in previous AF or non-AF patients. 8 In patients with chronic heart failure, only new-onset AF was also associated with increased death (hazard ratio 1.72), but not paroxysmal or chronic AF. 9 More recently, Batra et al in the Swedish registry study reported that AF was associated with a higher risk of MACE than sinus rhythm, irrespective of AF type (paroxysmal, persistent, chronic).…”
Section: Article P 1615mentioning
confidence: 99%